Diltiazem hydrochloride: New technologies and evolution of diltiazem - Glasser, Stephen P. (Clin Cardiol, 2009)
Graded extended‐release diltiazem (CARDIZEM® LA) (GRD) is a new formulation of diltiazem engineered to provide more precise blood pressure control than traditional antihypertensive agents. Unlike other diltiazem once‐daily formulations, CARDIZEM® LA is a tablet formulation. Its pharmacokinetic profile differs from that of CARDIZEM® CD, another extended‐release formulation of diltiazem, in that GRD exhibits a smoother drug‐release profile with a “one‐peak” plasma concentration time curve. Clinical results demonstrate therapeutic efficacy throughout its 24‐h dosing interval, regardless of time of administration; however, compared with morning administration, evening dosing results in significantly greater bioavailability, especially during the morning hours, when blood pressure is highest in most individuals. In hypertensive patients, GRD has demonstrated dose‐related efficacy superior to that of ramipril in patients with Stage I and II hypertension and superior to that of amlodopine in African American hypertensives during the critical morning period. In patients with chronic stable angina, evening doses of GRD have been shown to increase exercise tolerance and delay the time to onset of angina during the early morning hours and throughout the 24‐h dosing interval. Trials in patients with hypertension or angina have consistently demonstrated a side effect profile with GRD similar to that observed with placebo. Adverse events do not appear to be dose related up to the highest recommended dose of 540 mg/day. These trial results, demonstrating consistent 24‐h efficacy and excellent tolerability, suggest that GRD may be a beneficial option in the treatment of hypertension and angina.